Visualization of recombination-mediated damage bypass by template switching - Giannattasio, Michele; Zwicky, Katharina; Follonier, Cindy; Foiani, Marco; Lopes, Massimo; Branzei, Dana (Nature structural & molecular biology, 2014)
A combination of two-dimensional gel electrophoresis and EM is used to isolate and characterize multiple template-switching intermediates generated in budding yeast during replication of damaged DNA. Template switching (TS) mediates damage bypass via a recombination-related mechanism involving PCNA polyubiquitination and polymerase δ–dependent DNA synthesis. Using two-dimensional gel electrophoresis and EM, here we characterize TS intermediates arising in Saccharomyces cerevisiae at a defined chromosome locus, identifying five major families of intermediates. Single-stranded DNA gaps of 150–200 nt, and not DNA ends, initiate TS by strand invasion. This causes reannealing of the parental strands and exposure of the nondamaged newly synthesized chromatid, which serves as a replication template for the other blocked nascent strand. Structures resembling double Holliday junctions, postulated to be central double-strand break–repair intermediates but so far visualized only in meiosis, mediate late stages of TS before being processed to hemicatenanes. Our results reveal the DNA transitions accounting for recombination-mediated DNA-damage tolerance in mitotic cells and replication under conditions of genotoxic stress.